(untitled) (Journal of Current and Advance Medical Research, 2021)
Background: Various types of medical management are given for mastalgia in fibrocystic breast disease. Objective: The aim of this study was to compare the effects of different commonly used medical management options of mastalgia of fibrocystic breast disease on the quality of life of the respondents and their side effects as well. Methods: This prospective longitudinal study was carried out in Out-patients Department of General Surgery, Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka, Bangladesh from July 2018 to June 2019. The patients with fibrocystic breast disease were selected according to the eligibility criteria and are allocated to two groups by alternative random selection. In non-pharmacological treatments receiving group, lifestyle modification advices along with Evening Primrose Oil were given. On the other hand, in pharmacological treatment receiving group, Bromocriptine and Danazole were given according to some selection criteria of the patients. Response of treatments to each group & side effects were determined at one month, three months and six months follow up respectively. Results: A total number of 45 patients were recruited for this study. Majority of them presented with cyclical mastalgia (57.78%), bilateral mastalgia (60%) and mastalgia with lumpiness (44.4%). Among the patients who received non- pharmacological treatment, mastalgia improved in 34.78% cases and patients received pharmacological treatment, mastalgia improved in 72.73% cases. Different domains of quality of life were improved significantly in patients who received pharmacological treatment. Conclusion: In conclusion pharmacological management by Danazol or Bromocriptine has well tolerated to the patients. Journal of Current and Advance Medical Research, July 2021;8(2):95-99